1996
DOI: 10.3109/17453679609002333
|View full text |Cite
|
Sign up to set email alerts
|

Clavicular nonunion: 31/32 healed after plate fixation and bone grafting

Abstract: We report the long-term results in 32 patients with established nonunion of the clavicle; 15 treated with AO Dynamic Compression Plate and autologous cancellous bone graft and 17 treated with an AO reconstruction plate and autologous cancellous bone graft. The patients were followed up for a mean of 8 (4-21) years from injury and 7 (4-12) from non-union operation, both by clinical review and radiographs. 31/32 nonunions united successfully. One fracture which initially failed to unite was replated and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 11 publications
1
33
0
1
Order By: Relevance
“…Compression plating, bone grafting and early mobilization have been successful in several small series: Jupiter and Leffert (1987) reported 17/19 healed nonunions, Bradbury et al (1996) 31/32, Eskola et al (1986) 20122, Manske and Szabo (1985) 10/10 and Sanderhoff Olsen et al (1995) 15/16. We found comparably good function after Rushpin fixation and autogenous bone grafting, with only I failure in 14 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compression plating, bone grafting and early mobilization have been successful in several small series: Jupiter and Leffert (1987) reported 17/19 healed nonunions, Bradbury et al (1996) 31/32, Eskola et al (1986) 20122, Manske and Szabo (1985) 10/10 and Sanderhoff Olsen et al (1995) 15/16. We found comparably good function after Rushpin fixation and autogenous bone grafting, with only I failure in 14 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, blood and bone marrow are the most frequently transplanted materials (Allard et al, 1987;Pedrosa et at., 1989;Aglietti et al, 1991;Eggers and Meeder, 1994;Friend et al, 1995;Olsen et al, 1995;Arrington et al, 1996;Bradbury et al, 1996). Fresh autogenous bone grafts are preferred in orthotopic procedures because of their compatibility and efficacy.…”
Section: (C) Human Studiesmentioning
confidence: 99%
“…Both dynamic compression plate and reconstruction plate have given equally good results, but with latter it is easier to give contour to the complex form of the clavicle. 18 Low-contact dynamic compression plates appeared to be associated with significantly better upper-limb function throughout the year following surgery, earlier fracture union and return to work, and a reduced incidence of implantassociated symptoms when compared with a standard dynamic compression plate in 36 adults with symptomatic nonunion of the middle third of the clavicle. 13 Endrizziet al 23 concluded that a bone graft might not be necessary in most cases of clavicle nonunion.…”
Section: Discussionmentioning
confidence: 90%
“…The time between injury and surgery for nonunion was 8.13 months (range 4 months to 24 months). Preoperative radiographic score was done as per Lane and Sandhu scoring system 18 (Table 1).…”
Section: Methodsmentioning
confidence: 99%